STUDI KOMPARATIF PERMINTAAN BERAS DI MALANG COMPARATIVE STUDY OF RICE DEMAND IN MALANG - Kurniasih, Defa; Pudjiastuti, Agnes Quartina; Mutiara, Farah (Universitas Tribhuwana Tunggadewi, 2017)
This study aims to analyze the function of rice demand and the factors that influence it as well as price elasticity, income elasticity, and cross elasticity. The research location was set in Mulyoagung and Tlogomas Village. Data were analyzed by multiple linear regression models. The results showed the price of rice had an effect on the demand for rice in Tlogomas with price elasticity of 0,051, income elasticity of 0,006 and cross elasticity of -0,004. The factors of rice price, total income, and number of family members influence the demand for rice in Mulyoagung with price elasticity of 0,105, income elasticity of 0,367 and cross elasticity of 1,481. Penelitian ini bertujuan untuk menganalisis fungsi permintaan beras dan faktor ? faktor yang mempengaruhinya serta elastisitas harga, elastisitas pendapatan, dan elastisitas silang. Lokasi penelitian ditetapkan di Desa Mulyoagung dan Kelurahan Tlogomas. Data dianalisis dengan model regresi linier berganda. Hasil penelitian menunjukkan harga beras berpengaruh terhadap permintaan beras di Kelurahan Tlogomas dengan elasitisitas harga 0,051, elastisitas pendapatan 0,006 dan elastisitas silang -0,004. Harga beras, jumlah pendapatan, dan jumlah anggota keluarga berpengaruh terhadap permintaan beras di Desa Mulyoagung dengan elasitisitas harga 0,105, elastisitas pendapatan 0,367 dan elastisitas silang 1,481.